2003
DOI: 10.1159/000070857
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neuroinflammation and Microglial Activation in Alzheimer’s Disease with Radiolabelled PK11195 and Single Photon Emission Computed Tomography

Abstract: Objectives: Inflammation contributes to degeneration in Alzheimer’s disease (AD), not simply as a secondary phenomenon, but primarily as a significant source of pathology. [123I]iodo-PK11195 is a single photon emission computed tomography (SPECT) ligand for the peripheral benzodiazepine receptor, the latter being expressed on microglia (brain resident macrophages) and upregulated under inflammatory circumstances. The objectives were to assess AD inflammation by detecting [123I]iodo-PK1119… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(96 citation statements)
references
References 37 publications
0
95
0
1
Order By: Relevance
“…Steroidogenic assay results using C6 glioma rat cells showed that PK 11195 (40 µM) stimulated the formation of pregnenolone significantly [19] however at the same concentration PK 11195 suppressed the increase in pregnenolone accumulation caused by other specific PBR ligands such as FGIN-1-27 [50]. A study by Versijpt et al 2003 demonstrated that PK 11195 reduced the amount of inflammatory mediators, such as TNF α and nitric oxide (NO), released by activated microglia cells [51]. This indicates that PBR ligands may be able to alter biochemical processes in the brain and hence may have therapeutic benefits in certain neurological disorders.…”
Section: Benzothiazepinesmentioning
confidence: 99%
“…Steroidogenic assay results using C6 glioma rat cells showed that PK 11195 (40 µM) stimulated the formation of pregnenolone significantly [19] however at the same concentration PK 11195 suppressed the increase in pregnenolone accumulation caused by other specific PBR ligands such as FGIN-1-27 [50]. A study by Versijpt et al 2003 demonstrated that PK 11195 reduced the amount of inflammatory mediators, such as TNF α and nitric oxide (NO), released by activated microglia cells [51]. This indicates that PBR ligands may be able to alter biochemical processes in the brain and hence may have therapeutic benefits in certain neurological disorders.…”
Section: Benzothiazepinesmentioning
confidence: 99%
“…The cerebellum has been used previously (Groom et al, 1995;Banati et al, 1999;Versijpt et al, 2003;Gerhard et al, 2005a), while an unaffected region was chosen to approximate those areas that would be found by cluster analysis as used in several reports (Banati et al, 2000(Banati et al, , 2001Cagnin et al, 2001a, b;Gerhard et al, 2003;Turner et al, 2004). Both these reference regions might, however, not be 'perfect' as reference tissue, because increased specific binding in these structures cannot be excluded.…”
Section: Limitationsmentioning
confidence: 99%
“…Both [ 11 C](R)-PK11195 and [ 11 C]PK11195 have been used as positron emmision tomography (PET) tracers to study activated microglia in various neurologic disorders. It has been used to study stroke (Ramsay et al, 1992;Pappata et al, 2000;Gerhard et al, 2000Gerhard et al, , 2005a), Alzheimer's disease (Groom et al, 1995; Cagnin et al, 2001a;Versijpt et al, 2003), multiple sclerosis (Banati et al, 2000;Debruyne et al, 2002Debruyne et al, , 2003Versijpt et al, 2005) and various other diseases (Pappata et al, 1991; Banati et al, 1999Banati et al, , 2001Goerres et al, 2001;Cagnin et al, 2001bCagnin et al, , 2004Cicchetti et al, 2002;Gerhard et al, 2003Gerhard et al, , 2004Gerhard et al, , 2005bTurner et al, 2004Turner et al, , 2005Venneti et al, 2004;Henkel et al, 2004;Ouchi et al, 2005). Most studies have used a reference tissue approach to quantify binding, either by applying the simplified reference tissue model (SRTM) (Lammertsma and Hume, 1996) or by using uptake normalized to a reference region.…”
Section: Introductionmentioning
confidence: 99%
“…The TSPO ligand 11 C-PK11195 was one of the first PET ligands used for the imaging of activated microglia in various neurodegenerative diseases (16), and several clinical studies have been performed (17,18). Although 11 C-(R)-PK11195 has been widely used, its high levels of plasma protein binding, high levels of nonspecific binding, relatively poor blood-brain barrier permeability, and short half-life limit its use in routine brain imaging (19).…”
mentioning
confidence: 99%